Pengaruh Loyalty Program terhadap Keputusan Pembelian Kopi Kenangan Makassar - Dardina Julianti; Tenri Sayu Puspitaningsih Dipoatmodjo; Muh. Ichwan Musa; Muh. Ilham Wardhana Haeruddin; Ilma Wulansari Hasdinansa (Pusat Riset dan Inovasi Nasional, 2024)
This research is quantitative research which aims to determine the influence of the Loyalty Program on the decision to purchase Kenangan Coffee. The independent variable in this research is the Loyalty Program, while the dependent variable is the purchasing decision. The population in this study was all customers of memorable coffee. Using the sampling method, a sample of 80 respondents was obtained. The data collection technique used was a questionnaire. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) v. 13. The results of this research show that the Loyalty Program (X1) has a positive and significant effect on purchasing decisions (Y). This means that the better the implementation of the loyalty program carried out by Memoria Coffee, the more consumer behavior towards making purchases will increase. vice versa